Study on the impact of the reserved length of the membranous urethra during laparoscopic radical prostatectomy on the recovery of urinary control function in patients - Li, Chuanbo; Lin, Rui; Bai, Qiulei; Guo, Huaiyuan (Frontiers in Surgery, 2025)
BackgroundProstate cancer is a common malignant tumor in the male urogenital system, and laparoscopic radical prostatectomy (LRP) is the standard surgical procedure for early-stage patients. However, postoperative urinary incontinence remains a major complication. The membranous urethra and its surrounding sphincters play a critical role in urinary continence, but the impact of their preserved length on postoperative recovery of urinary continence function remains unclear.ObjectiveTo investigate the effect of the preserved length of the membranous urethra during LRP on early and long-term recovery of urinary continence function in patients.MethodsA retrospective analysis was conducted on 160 patients who underwent LRP from March 2023 to June 2024. The patients were divided into a long-segment group (preserved length ≥15 mm, 90 cases) and a short-segment group (preserved length <15 mm, 70 cases) based on the preserved length of the membranous urethra. The International Continence Society criteria were used to evaluate the urinary continence recovery rate (≤1 pad/day) at 1, 3, 12, and 24 months postoperatively, and differences between the two groups were compared.ResultsBaseline characteristics were comparable between long-segment (≥15 mm, n = 90) and short-segment (<15 mm, n = 70) groups (P > 0.05). The long-segment group demonstrated significantly superior urinary continence recovery at all time points (P < 0.05): At 1 month, pad-based recovery (38.9% vs. 25.7%) and PGI-I improvement (41.1% vs. 28.6%); at 3 months (61.1% vs. 42.9%; 65.6% vs. 47.1%); at 12 months (77.8% vs. 64.3%; 80.0% vs. 67.1%); and at 24 months (88.9% vs. 78.6%; 91.1% vs. 81.4%). Notably, patients receiving bilateral nerve-sparing with long urethral preservation achieved optimal outcomes (94.3% pad-based recovery; 96.2% PGI-I improvement), significantly surpassing other nerve-sparing approaches (P < 0.05).ConclusionPreserving the length of the membranous urethra ≥15 mm during LRP can significantly promote the recovery of early and long-term urinary continence function, providing a basis for precise surgical operations in clinical practice. Future studies with larger sample sizes and longer follow-up periods are needed for validation.